Development of SCAR Markers for Identification of Perennial and Annual Types in the Asian Wild Rice - Preecha Prathepha, (Agriculture and Natural Resources, 2002)
Asian wild rice, Oryza rufipogon Griff., is recognized as wild progenitor of Asian cultivated rice (O. sativa). This species tends to differentiate into annual and perennial types. In order to help establish a basis for the identification of the two types of this species, the SCAR markers have been developed. A total of 20 random primers were screened among 60 individuals of each type using random amplified polymorphic DNAs (RAPDs). One diagnostic PCR product for each type was isolated, sequenced and converted to sequence characterized amplified region (SCAR). The SCAR primer pairs (OPAM10-900F/R) were able to amplify the specific DNA fragments from the DNA of the perennial type but not from the DNA of the annual type. The amplified fragment operated by that was specify to perennial type could be used as a rapid means of identifying the perennial type from annual type of O. rufipogon. The other single unique fragment occurring in both types of O. rufipogon and O. sativa was generated by the second SCAR primer pairs (OPAM10-800F/R). This evidence supports the idea that the progenitor of the cultivated species is assumed to be O. rufipogon. Furthermore, the nucleotide sequences from the fragment may be useful to elucidate the evolutionary relationships within A genome of Oryza species.